2018
DOI: 10.20944/preprints201808.0049.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intelligent Land Vehicle Model Transfer Trajectory Planning Method Based on Deep Reinforcement Learning

Abstract: Aiming at the problem of model error and tracking dependence in the process of intelligent vehicle motion planning, an intelligent vehicle model transfer trajectory planning method based on deep reinforcement learning is proposed, which obtain an effective control action sequence directly. Firstly, an abstract model of the real environment is extracted. On this basis, Deep Deterministic Policy Gradient (DDPG) and vehicle dynamic model are adopted to jointly train a reinforcement learning model, and to decide t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…According to the path planning process, a self-driving car should consider all possible obstacles that are present in the surrounding environment and calculate a trajectory along a collision-free route. As stated in Shalev-Shwartz, Shammah, and Shashua DRL for path planning deals mainly with learning driving trajectories in a simulator (Panov, Yakovlev, & Suvorov, 2018;Paxton et al, 2017;Shalev-Shwartz et al, 2016;L. Yu et al, 2018).…”
Section: Deep Learning For Path Planning and Behavior Arbitrationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the path planning process, a self-driving car should consider all possible obstacles that are present in the surrounding environment and calculate a trajectory along a collision-free route. As stated in Shalev-Shwartz, Shammah, and Shashua DRL for path planning deals mainly with learning driving trajectories in a simulator (Panov, Yakovlev, & Suvorov, 2018;Paxton et al, 2017;Shalev-Shwartz et al, 2016;L. Yu et al, 2018).…”
Section: Deep Learning For Path Planning and Behavior Arbitrationmentioning
confidence: 99%
“…However, Pendleton et al (2017) do not include a review on deep learning technologies, although the state-of-the-art literature has revealed an increased interest in using deep learning technologies for path planning and behavior arbitration. Following, we discuss two of the most representative deep learning paradigms for path planning, namely IL (Grigorescu, Trasnea, Marina, Vasilcoi, & Cocias, 2019; Rehder, Quehl, & Stiller, 2017; Sun, Peng, Zhan, & Tomizuka, 2018) and DRL-based planning(Paxton, Raman, Hager, & Kobilarov, 2017;L. Yu, Shao, Wei, & Zhou, 2018).The goal in ILRehder et al, 2017;Sun et al, 2018) is to learn the behavior of a human driver from recorded driving experiences(Schwarting, Alonso-Mora, & Rus, 2018).…”
mentioning
confidence: 99%
“…Owing to impressive advantages in extracting features, deep learning is promising to overcome the bottlenecks of conventional planning algorithms and learn to plan paths efficiently under various conditions for self-driving cars. For example, Yu et al [79] proposed a path planning method based on deep reinforcement learning. This method can deal with the problem of the model training with continuous input and output.…”
Section: Path Planningmentioning
confidence: 99%
“…The flow chart of the method proposed in [79] is shown in Figure 18. There are an actor policy network and a critic evaluation network.…”
Section: Path Planningmentioning
confidence: 99%
“…A deep learning path planning algorithm for autonomous driving is proposed in [6]. The method addresses the problem of error modeling and path tracking dependencies.…”
Section: Related Workmentioning
confidence: 99%